Optimal allocation of means for trauma prevention using stochastic programming - Vakrinienė, Sigutė; Čyras, Petras (Lietuvos matematikos rinkinys, 2002)
Optimal criterion for allocation of means necessary for trauma prevention is proposed. The problem is simulated as a matrix game with random elements.